Measuring real-financial connectedness in the U.S. economy - Erhan Uluceviz; Kamil Yılmaz (Koç University-TÜSİAD Economic Research Forum (ERF), 2018)
We analyze connectedness between the real and financial sectors of the U.S. economy. Using the weekly ADS index of the Philadelphia FED (the widely used business conditions indicator) to represent the real side, we find that during times of financial distress and/or business cycle turning points the direction of connectedness runs from the real sector to financial markets. The ADS index is derived from a model containing a measure of term structure along with real variables, therefore, it might not be the best representative of the real activity to be used in the connectedness analysis. As an alternative, we derive a real activity index (RAI) from a dynamic factor model of the real sector variables only. The behavior of RAI over time is quite similar to that of the ADS index. When we include RAI to represent the real side of the economy in the connectedness analysis, the direction of net connectedness reverses: financial markets generate positive net connectedness to the real side of the economy.
Keywords: C38; E44; E37; G10; 330; Macro-financial linkages; Connectedness; ADS index; Dynamic factor model; Volatility; Vector autoregression; Variance decomposition